Pemanfaatan Maggot Untuk Lingkungan Dan Ekonomi Keluarga, Kelurahan Anggut Dalam,Kecamatan Ratu Samban Kota Bengkulu - Refo Elfianza; Muhammad Fikri; Aprianti Lubis; Glori Pesta Pince Sitorus; Entin Oktantia Safitri; Fadhiil Ahmadi; Ulfiyah Mei; Yulanda Nurul Fadhila; Hafidza Zia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The issue of organic waste in urban areas is an urgent environmental problem that requires immediate attention. One innovative solution that is increasingly being implemented is the cultivation of maggots (Black Soldier Fly larvae/BSF), which function as agents for decomposing organic waste and producing economically valuable products. The Community Service Learning (CSL) activity conducted by students from Bengkulu University in Anggut Dalam Village, Ratu Samban Subdistrict, Bengkulu City, aims to introduce and implement maggot farming as an effort to manage waste and empower family economies. This article comprehensively discusses the implementation stages, results, challenges, and social and economic impacts of the maggot farming program in the community. The results of the activity show an increase in environmental awareness, a reduction in the volume of organic waste, and the emergence of new income sources for families. Maggot farming has proven to be an environmentally friendly solution with the potential to improve community well-being sustainably.